The Role of the Tourism Office in the Development of Binusan Waterfall Nature Tourism Destinations, Nunukan Regency, North Kalimantan Province - Nurindah Indah (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2022)
Purpose: To determine the role of the Department of Tourism in the development of natural tourism destinations of Binusan Waterfall, Nunukan Regency, and also to determine the supporting factors and inhibiting factors in the development of natural tourism destinations of Binusan Waterfall. Methods: In this study, the data collection process was carried out by observation, interviews, and documentation. While the analysis process uses an interactive model according to Miles & Huberman, namely data collection, data reduction, data presentation, and drawing conclusions. Results: This study found that the role of the Tourism Office in the development of natural tourist destinations of Binusan Waterfall based on 3A (attractions, amenities, and accessibility) was sufficient, there were natural tourist attractions, namely the beautiful environment and views of the Binusan waterfall, cultural attractions, namely Tidung culture, and Dayak, as well as man-made attractions, namely tourism infrastructure such as a bridge to the Binusan waterfall, and currently in development planning, namely the addition of attractions, namely the flying fox, adequate amenities such as toilets & bathrooms, places of worship, gazebos, counters, parking lots, entertainment stages, accessibility that is easily accessible is already dominant with paved roads. The supporting factor for the Binusan Waterfall tourist destination is the support of the government and several community leaders to increase the role of the Tourism Office with other tourism communities in order to be able to optimize human resources in improving the community's business economy and contribute more to the development of the tourism sector in Nunukan Regency. The inhibiting factors in the management of Binusan Waterfall are related to the budget for object development and not all communities are moved to take an active role in the development of tourist destinations, the lack of professional human resources, and the need for more attention from the Nunukan Regency Tourism Office in improving human resources competently. Contribution: This study provides a description of the development of 3A (attractions, amenities, and accessibility) through the role of the Tourism Office in the natural tourist destination of Binusan Waterfall, Nunukan Regency.